Growth phase diets diminish histone acetyltransferase Gcn5 function and shorten lifespan of Drosophila males. - Mizutani, S.; Furuya, K.; Mure, A.; Takahashi, Y.; Mori, A.; Sakurai, N.; Suito, T.; Nagao, K.; Umeda, M.; Watanabe, K.; Hattori, Y.; Uemura, T. (EMBO Reports, 2025)
The nutritional environment in early life, referred to as the nutrition history, exerts far-reaching health effects beyond the developmental stage. Here, with Drosophila melanogaster as a model, we fed larvae on diets consisting of a variety of yeast mutants and explored the resulting histories that impacted adult lifespan. A larval diet comprised of yeast nat3 KO shortened the lifespan of male adults; and remarkably, this diet diminished the function of histone acetyltransferase Gcn5 in larvae. Concordantly, perturbation of Gcn5-mediated gene regulation in the larval whole body or neurons significantly contributed to the earlier death of adults. The nat3 KO diet is much more abundant in long-chain fatty acids and branched-chain amino acids (BCAAs) than the control yeast diet. Supplementing the control diet with a combination of oleic acid, valine, and acetic acid recapitulated the effects of the nat3 KO diet on the larval transcriptome and the lifespan of males. Our findings strongly suggest a causal link between a fatty acids- and BCAA-rich diet in developmental stages and lifespan reduction via the adverse effect on the Gcn5 function.